LOW BACK PAIN AMONG PATIENTS AGED ≥ 12 YEARS RECEIVING PHYSIOTHERAPY SERVICES IN A REFERRAL HOSPITAL IN RWANDA - Mukamisha Monique, Dr. Japheths Ogendi, Dr. Michael Habtu (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Background: Lower back pain, or Global Burden Disease (GBD), is underestimated in treatment. Rwanda studies show its prevalence: 78% of nurses in 2010, and 45.8% in 2021. Individual traits, work conditions, and psychosocial factors contribute to its development, highlighting the multifaceted nature of this condition. Aim: This study aimed to determine the prevalence of lower back pain and its associated factors among patients aged twelve and above receiving physiotherapy services at Kibungo Level II Teaching Hospital Materials and Methods: Quantitative methods were employed, with interviews and questionnaires conducted with eligible patients, following ethical procedures. The collected data were analyzed using SPSS version 22, utilizing descriptive statistics, chi-square tests, and multivariate logistic regression. Results: The results revealed a high prevalence of lower back pain, with 73.9% of patients experiencing this condition. Significant associations were observed between lower back pain and certain factors such as age (33-54 years old), occupation as a farmer, lack of education, and diabetes. Conclusion: The study highlights the necessity of interventions in addressing lower back pain and its factors among physiotherapy patients. It recommends mechanized farming to prevent farmer back pain and stresses the role of policymakers and healthcare providers in mitigating this issue effectively.